Case Report: Diagnosis of Human Alveolar Echinococcosis via Next-Generation Sequencing Analysis - Li, Ke; Ma, Yubao; Ban, Rui; Shi, Qiang (Frontiers in Genetics, 2021)
Introduction: Alveolar echinococcosis (AE) is a rare parasitic disease caused by the infection of Echinococcus multilocularis. AE may mimic malignancy both in clinical presentation and radiological imaging, which is often misdiagnosed as metastatic tumor. Recently, next-generation sequencing (NGS) technologies are increasingly being used to address a diverse range of biological questions. Here, we describe a rare case of alveolar echinococcosis diagnosed by pan-pathogen screening, using next-generation sequencing. To the best of our knowledge, this is the first reported case of AE which was definitely diagnosed relying NGS of cerebrospinal fluid (CSF). Case presentation: A 33-year-old man presented with repeat seizure and progressive headache for six months. Head magnetic resonance imaging (MRI) showed multiple masses with edema. Lung and abdominal computer tomography (CT) revealed multiple masses in bilateral lung, liver and the right adrenal gland. Bacterial, tuberculosis and fungal infection were excluded by CSF examination. Repeated target biopsy on the masses in the lung and liver showed as fibrous connective tissue without positive findings. NGS of CSF was performed and detected nucleic acid sequences of Echinococcus multilocularis. Consequently, the patient has accepted 1-year albendazole therapy. His case was followed up through imaging procedures. Conclusion: The next-generation sequencing of CSF is a reliable and sensitive diagnostic method for the detection of pathogenic microorganisms, and may allow the accurate diagnosis of alveolar echinococcosis. In view of this case, we recommend NGS as a potential tool for diagnosis of cerebral AE, especially if repeated biopsies are negative. Keywords: Alveolar echinococcosis, Next-generation sequencing, adrenal gland, Echinococcus multilocularis, diagnosis